ALLIANCE DES ÉTATS DU SAHEL (AES) AND THE CHALLENGE OF FOOD SECURITY: A POLITICAL ANALYSIS OF SECURITY IN THE SUB-SAHARAN REGION - Roudhoh Said; Yafi Alghiffari; Dwi Ardiyanti (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
The Alliance of Sahel States (AES), comprising Mali, Niger, and Burkina Faso, was formed amid geopolitical tensions and multidimensional crises gripping the Sub-Saharan region. Political instability resulting from military coups, armed conflicts, international sanctions, and the impacts of climate change have exacerbated food security challenges in the region. This study aims to analyse the link between political-security dynamics and food security in the AES region, and to evaluate the alliance's role in addressing complex humanitarian challenges and international relations. Using a qualitative approach with a desk study method, data were analysed through the framework of non-traditional security theory and the Regional Security Complex Theory (RSCT) by Barry Buzan and Ole Wæver. The findings indicate that a militaristic approach to food distribution, diplomatic isolation following the ECOWAS exit, and dependence on external actors such as Russia have deepened the crisis and weakened civilian capacity in the long term. Therefore, alternative strategies based on civilian development and more inclusive multilateral cooperation are needed to build sustainable food security and strengthen human resources in the Sahel region.